Kinetic simulations of laser filamentation in plasmas - E. M. Epperlein (Physics of Fluids B: Plasma Physics, 1991)
The effects of nonlocal electron heat transport on the nonlinear evolution of both thermal and ponderomotive laser filamentation in plasmas have been modeled using the Fokker–Planck (FP) code spark. The code solves the FP equation for electrons, the full hydrodynamic equations for cold ions, and the paraxial wave equation for laser light, in Cartesian geometry. Filamentation simulations, under the experimental conditions reported by Young et al. [Phys. Rev. Lett. 61, 2336 (1988)], confirm recent theoretical predictions [E. M. Epperlein, Phys. Rev. Lett. 65, 2145 (1990)] that the kinetic thermal mechanism should dominate over the ponderomotive one. It is further demonstrated that it is important to include the ion hydrodynamics.